Copywriting Structure Based on Direct Persuasive in Instagram Posts of Hari Peduli Sampah Nasional 2024 Komunitas Ciliwung Depok - Dian Nurdiansyah; Shafa Kamiliya; Melody; Febriyanti (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2024)
In the digital age, copywriting strategies also need to adapt to the popular trends and language among the target audience. Audiences on Instagram, especially the younger generation, are more interested in casual, interactive, and personalized language styles. Copywriting as a persuasive technique and communication strategy has become one of the most effective tools in the digital age, especially on platforms like Instagram. The copywriting structure consists of a headline, tagline (subheadline), body copy, and call to action (CTA), all of which will be integrated into one unit and encourage the audience to understand the message conveyed. The use and clarity of the copywriting structure on “Komunitas Ciliwung Depok” as an environmental care community in addition to having a direct existence, they also form a virtual-based community with an Instagram account. The content of the National Waste Care Day 2024 is the object of research that discusses the structure of copywriting; this is based on the consideration that the existence of waste is often a major problem for humans due to acts of indifference to the environment and ecosystems, especially river ecosystems which play a vital role for human life in fact. In this study, researchers used a qualitative approach with virtual observation techniques and documentation to collect data while in the field and peer debriefing to validate field findings (data). This ensured that the research results could be measured and were highly independent, not related to or affected by conditions that make this research biased.